Efficacy and safety of eribulin as first- to third-line treatment in patients with advanced or metastatic breast cancer previously treated with anthracyclines and taxanes. (April 2017) - Maeda, Shigeto; Saimura, Michiyo; Minami, Shigeki; Kurashita, Kaname; Nishimura, Reiki; Kai, Yuichiro; Yano, Hiroshi; Mashino, Kohjiro; Mitsuyama, Shoshu; Shimokawa, Mototsugu; Tamura, Kazuo
Abstract: Objectives: Despite the survival benefit and acceptable tolerability of eribulin for advanced/metastatic breast cancer (MBC) patients pretreated with anthracyclines and taxanes, there is limited evidence of the clinical benefit of early eribulin use. We investigated the efficacy and safety of first- to third-line eribulin use in patients with MBC. Materials and methods: In this phase II, open-label, single-arm study conducted at 14 sites in Kyushu, Japan, women with histologically confirmed human epidermal growth factor receptor 2–negative MBC were enrolled between December 1, 2011 and November 30, 2013 (Data cut-off: November 30, 2014). Objective response rate (ORR; primary endpoint), disease control rate (DCR), progression-free survival (PFS), duration of response (DOR), overall survival (OS), and safety were evaluated. Results: Of 53 recruited patients, 47 were enrolled. The ORR was 17.0% (95% confidence interval, 7.6–30.8), DCR was 66.0% (51.2–77.8), median PFS was 4.9 months (3.5–7.0), DOR was 6.6 months (1.9–14.3), and median OS was 17.4 months (10.1–not evaluable). The common grade 3/4 adverse events were neutropenia (25 patients; 53.2%), leucopenia (16 patients; 42.1%) and febrile neutropenia (4 patients; 8.5%). Toxicity did not increase during the long-term treatment. Subgroup analysis indicated that first-line treatment led to higher ORR and prolonged PFS and OS than second-/third-line treatment and that incidence of adverse events in patients of second-/third-line treatment was not higher than that in patients of first-line treatment. Conclusion: Eribulin exhibited efficacy and manageable tolerability in Japanese women with pretreated MBC in first- to third-line use. (ID: UMIN000007121). Highlights: In phase II trial, Japanese women with metastatic breast cancer received eribulin. Eribulin (first- to third-line) demonstrated efficacy and manageable tolerability. First-line treatment led to higher objective response rate than second-/third-line. First-line treatment also led to prolonged progression free and overall survival.